Caspase-independent cell engulfment mirrors cell death pattern in Drosophila embryos. - Mergliano, J.; Minden, J.S. (Development, 2003)
Programmed cell death plays an essential role during Drosophila embryonic development. A stereotypic series of cellular changes occur during apoptosis, most of which are initiated by a caspase cascade that is triggered by a trio of proteins, RPR, HID and GRIM. The final step in apoptosis is engulfment of the cell corpse. To monitor cell engulfment in vivo, we developed a fluorogenic beta-galactosidase substrate that is cleaved by an endogenous, lysosomal beta-galactosidase activity. The pattern of cell engulfment in wild-type embryos correlated well with the known pattern of apoptosis. Surprisingly, the pattern of cell engulfment persisted in apoptosis-deficient embryos. We provide evidence for a caspase-independent engulfment process that affects the majority of cells expected to die in developing Drosophila embryos.